O professor que queremos - Manaia, Gustavo Fitas; Ciancaglini, Jaqueline Victória; Sugawara, Lucy Miwa; Geraldo, Mariana de Sousa Prado; Vieira, Thaiane Fagundes (ABCS Health Sciences, 2015)
Não se aplica